2006
DOI: 10.1063/1.2195087
|View full text |Cite
|
Sign up to set email alerts
|

Possible performance improvement in [2]catenane molecular electronic switches

Abstract: Mechanically interlocked bistable supramolecular complexes are promising candidates of molecular electronics. Applying a multiscale computational approach, here we study the coherent charge transport properties of catenane monolayers sandwiched between Cu͑111͒ electrodes. We demonstrate the robust nature of electrical switching behavior with respect to the variations in the monolayer packing density and the type of electrodes, as well as the thermal fluctuations of the molecules. We propose that the asymmetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…As described in section 3.2, however, we found that HOMO has the DNP (rather than TTF) origin within our calculations. This is the major difference between the present rotaxane device model and previous catenane device models. , We found a similar assignment in the five out of the total eight GSCC models that were used to obtain the average I − V curve shown in Figure . This is in contrast to our finding for the catenane device case, where all the models we considered had TTF-originated HOMO .…”
Section: Resultssupporting
confidence: 63%
“…As described in section 3.2, however, we found that HOMO has the DNP (rather than TTF) origin within our calculations. This is the major difference between the present rotaxane device model and previous catenane device models. , We found a similar assignment in the five out of the total eight GSCC models that were used to obtain the average I − V curve shown in Figure . This is in contrast to our finding for the catenane device case, where all the models we considered had TTF-originated HOMO .…”
Section: Resultssupporting
confidence: 63%
“…For this study, we used the DREIDING force field as previously used to study Nafion ,,, and Dendrion , as well as various molecular systems such as hydrogel, liquid–liquid and liquid–air interfaces, , and molecular self-assembly. The water was described using the F3C force field . These force field parameters were reported in the original papers ,, and in our previous study on hydrated Nafion.…”
Section: Modeling and Simulationsmentioning
confidence: 99%
“…[88][89][90][91][92][93][94][95] The water is described using the F3C force field. 96 The force field parameters are reported in the original papers 75 96 97 and in our previous study 29 on hydrated Nafion.…”
Section: Force Field and MD Simulationsmentioning
confidence: 99%